Strengths of primary healthcare regarding care provided for chronic kidney disease - Elaine Amaral de Paula; Mônica Barros Costa; Fernando Antonio Basile Colugnati; Rita Maria Rodrigues Bastos; Chislene Pereira Vanelli; Christiane Chaves Augusto Leite; Márcio Santos Caminhas; Rogério Baumgratz de Paula
ABSTRACT Objective: to assess the structure and results obtained by the "Chronic Renal Patients Care Program" in a Brazilian city. Method: epidemiological, cross-sectional study conducted in 14 PHC units and a secondary center from 2010 to 2013. The Donabedian Model was the methodological framework used. A total of 14 physicians, 13 supervisors, and 11 community health agents from primary healthcare were interviewed for the assessment of structure and process and 1,534 medical files from primary healthcare and 282 from secondary care were consulted to assess outcomes. Results: most units lacked sufficient offices for physicians and nurses to provide consultations, had incomplete staffing, and most professionals had not received proper qualification to provide care for chronic renal disease. Physicians from PHC units classified as capable more frequently referred patients to the secondary care service in the early stages of chronic renal disease (stage 3B) when compared to physicians of units considered not capable (58% vs. 36%) (p=0.049). Capable PHC units also more frequently presented stabilized glomerular filtration rates (51%) when compared to partially capable units (36%) and not capable units (44%) (p=0.046). Conclusion: patients cared for by primary healthcare units that scored higher in structure and process criteria presented better clinical outcomes. Objective: to identify the coping strategies of family members of patients with mental disorders and relate them to family member sociodemographic variables and to the patient's clinical variables. Method: this was a descriptive study conducted at a psychiatric hospital in the interior of the state of São Paulo, with 40 family members of hospitalized patients over the age of 18, and who followed the patient before and during hospitalization. We used tools to characterize the subjects and the Folkman and Lazarus Inventory of Coping Strategies. Results: the coping strategies most often used by family members were social support and problem solving. Mothers and fathers used more functional strategies (self-control p=0.037, positive reappraisal p=0.037, and social support p=0,021). We found no significant differences between the strategies and other variables examined. Conclusion: despite the suffering resulting from the illness of a dear one, family members make more use of functional strategies, allowing them to cope with adversities in a more well-adjusted way.